Risk factors for further recurrences of Clostridioides difficile infection at the first and second recurrence: a retrospective cohort - Måns Stefansson; Oscar Bladh; Piotr Nowak; Lars Rombo; Magnus Hedenstierna; Johan Ursing (BMC Infectious Diseases)
Abstract Background Recurrent Clostridioides difficile infection is most effectively treated with faecal microbiota transplantation. Swedish and European guidelines suggest faecal microbiota transplantation after a first or second recurrence, respectively. The aims of this study were to evaluate risk factors for further relapses at the first and second recurrence, related to treatment recommendations. Methods Patients aged ≥ 18 years with two positive tests for C. difficile within eight weeks and treated at the study hospitals during 2014–2022 were eligible for inclusion. Retrospectively collected data included age, sex, treatment, and clinical characteristics for each episode. Risk factors for further recurrences at the first and second recurrence were identified using multivariable logistic regression analysis. Results The median age in the total cohort (n = 231) was 76 (IQR 67–84) years, 52% were females and 15% were healthy without comorbidities. One recurrence only occurred in 110 patients (48%), however, no clinically significant risk factors predicting more than one recurrence were identified. Two or more recurrences occurred in 110 patients, of whom, 44 (40%) had further recurrences. Frailty (Clinical Frailty Scale ≥ 4) was significantly associated with more than two recurrences (p = 0.03). The respective median times between the first and the second recurrences were 12 and 17 days in patients with more than two recurrences compared to two recurrences only (p = 0.02). Conclusions Patients experiencing a second recurrence of C. difficile infection who were frail and relapsed in a shorter time span after the first recurrence had a significantly increased risk of further recurrences.